Establishment and application of a loop-mediated isothermal amplification method based on MetAP2 gene for the detection of Nosema bombycis in silkworms (Bombyx mori) - Qazi, Izhar Hyder; Yuan, Ting; Yang, Sijia; Angel, Christiana; Liu, Jiping (Frontiers in Veterinary Science, 2025)
Pebrine, caused by Nosema bombycis, is a devastating disease of silkworms that causes huge economic losses to the sericulture farmers. Although pebrine is a quarantine disease, currently the development of effective molecular diagnostic or therapeutic tools for its management is still a lagging hotspot in sericulture research. In the present study, a highly specific, sensitive, and field-applicable LAMP assay targeting MetAp2 gene was developed. LM1 primer set produced better results, with fluorescence (amplification) signals appearing in ~50 min. The reaction temperature of 60.9°C and outer primer to inner primer ratio of 1:8 were found to be optimal, with the shortest amplification time and strongest fluorescence intensity. The LAMP assay showed high specificity for the DNA of Nosema bombycis spores, as the templates of other common microorganisms of silkworms showed no amplification. The LAMP assay detected pMD-19T-met positive plasmid at the lowest concentration of 103 copies, with a detection time of ~80 min. The practicality test showed that the LAMP assay can detect Nosema bombycis spore DNA at the lowest concentration of 10−3 ng/μL. At concentration of 1.2 ng/μL, the real-time fluorescence signals appeared in ~60 min. The LAMP assay detected Nosema bombycis at all life stages of untreated silkworms. In fumagillin treated silkworms, no real-time fluorescence amplification was observed at 90 h and later, indicating the reliability of LAMP in detecting Nosema bombycis, and effectiveness of fumagillin, to some degree, in treating pebrine infection. The developed LAMP assay holds good promise for its application as a specific and field-applicable tool for the detection/control of pebrine in the field settings.